A Thematic Analysis of Advertisement in the Telecommunication Industry - Esther Amah; Olaleke Oluseye Ogunnaike; Adebanji William Ayeni; Mercy Ojo (Binus Business Review, 2017)
The main objective of this research was to determine the types of appeals used in telecommunication advertisement, explain how the themes and appeals used in the advertisement were presented, and see how it could attract subscribers despite the challenges in the industry. Qualitative content analysis method was used to provide a thematic analysis of the messages contained in numbers of selected advertisements shown on YouTube, social media, and television stations in Nigeria. The findings show that the advertisements adopt emotional (love, celebrity appearance, music, comedy, humor, drama) and rational appeal to persuade the subscribers. Moreover, the themes of the advertisements focus on accomplishment and improve service regarding call charges, network coverage, network quality, and customer service. It further shows that these strategies employed by the telecommunication industry are capable of influencing the choice of the subscribers in the Nigerian market. The research recommends and concludes that companies should consistently engage the appeals used with more emphasis on the emotional appeal to retain their size of the market.